When follower believe in co-production leadership: why do personal characteristics matters? - Sinto Sunaryo; Joko Suyono; Sarjiyanto Sarjiyanto; Adnan Effendi; Risgiyanti Risgiyanti (Jurnal Siasat Bisnis, 2022)
Purpose – The present study aims to analyze personal characteristics that potentially affect the belief in co-production leadership and its effect on behavior based on the belief. This study also attempted to determine the impact of the leadership romance role on the relationship between coproduction leadership and the intention to obey the leader. Design/methodology/approach – The research used a survey method with a quantitative approach. Out of 250 distributed questionnaires, only 149 questionnaires met the criteria. Partial Least Square Structural Equation Modelling (PLS-SEM) was used to test the proposed hypotheses. Findings – The result of the study showed that the values of collectivism positively associated with the co-production leadership belief. However, the study also found that the values of individualism had no significant effect on the co-production leadership belief. Surprisingly, the result also showed that the co-production leadership belief positively affected the leader's intention to obey. Research limitations/implications – This study addressed political parties as the object of the study, so thoroughness in generalizing the result of the study to other objects is needed. The study's design is cross-sectional, which limits the researcher's in-depth analysis of workplace violence phenomena since the data being studied is only based on one period of time. Lastly, the data for analysis were limited to the respondents’ responses to statements in the questionnaire. More information could be obtained by conducting an in-depth interview with the respondents. Practical implications – The result of this study indicated that the romance of leadership moderates the relationship between the co-production leadership and the intention to obey the leader. This study opens new avenues for research on organizational cynicism and carries implications for theory and practice. Originality/value – This study attempts to answer the question about whether each individual with different characteristics (high values on individualism-collectivism) possess a different belief related to followership role orientation (i.e. co-production leadership). The study also examines whether this belief determines followers' behavior on leadership process.